The dynamics of economic vulnerability: A comparative European analysis - Christopher T. Whelan; Bertrand Maître (The Economic and Social Research Institute (ESRI), 2007)
A joint concern with multidimensionality and dynamics is a defining feature of the pervasive use of the terminology of social exclusion in the European Union. The notion of social exclusion focuses attention on economic vulnerability in the sense of exposure to risk and uncertainty. Sociological concern with these issues has been associated with the thesis that risk and uncertainty have become more pervasive and extends substantially beyond the working class. We combine features of recent approaches to explicit statistical modelling of poverty dynamics and multidimensional deprivation in order to develop our understanding of the dynamics of economic vulnerability. An analysis involving nine countries and covering the first five waves of the European Community Household Panel shows that, across nations and time, it is possible to identify an economically vulnerable class. This class is characterised by heightened risk of falling below a critical resource level, exposure to material deprivation and experience of subjective economic stress. The application of dynamic analysis shows that cross-national differentials in persistence of vulnerability are wider than in the case of income poverty and less affected by measurement error. Economic vulnerability profiles vary across welfare regimes in a manner broadly consistent with our expectations. Variation in the impact of social class within and across countries provides no support for the argument that its role in structuring such risk has become much less important.
Keywords: 330; Social Exclusion; Dynamics; Multidimensionality; Vulnerability; Latent Class; Soziale Isolation; Soziale Lage; Armut; Multivariate Analyse; Europa